Innovative system for monitoring health indicators with virtual assistance for elderly people with visual limitations - Jimenez-Cortez, Carolina; Alvarez-Ventocilla, Yevit; Rubiños-Jimenez, Santiago; Vallejos-Zuta, Alex; Ipince-Antunez, Daniel; Vilcahuaman-Sanabria, Raul; Tabacchi-Murillo, Jesus (LACCEI, 2024)
The objective of the study was to develop a vital signs alert and monitoring system with virtual assistance, to improve the care provided to older people with visual disabilities. The methodology used in the research consisted of the application of the applied method, with an experimental design and a quantitative approach. The population studied is in the constitutional province of Callao and consisted of a group of 10 older adults with visual disabilities. Information was collected from the instruments used in data collection. Among the positive results obtained, the voluntary participation of 10 older adults with visual disabilities in a test of the prototype of the vital signs monitoring system with virtual assistance stands out. The average score achieved in this evaluation is 4.9, which indicates that our approval rate is 81.7%. It has been concluded that the design contributes to improving the care provided to older adults with visual disabilities.